Internalisasi Sikap Moderat Dalam Perkuliahan pada mahasiswa di Era Milenial - Rosyadi, Zainal; Nu'man, Moh; Zamroji, Nanang; Rouf, Abd.; Pratama, Mohammad Putra (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is as a solution for internalizing moderate attitudes which can be achieved through increasing student awareness of the values ​​of moderation, the effective use of technology in learning, and the important role of extracurricular activities. This research uses a holistic and interdisciplinary approach that combines the disciplines of education, psychology, sociology, and information technology. This research utilizes qualitative methods through in-depth interviews, participant observation, and documentation analysis. The internalization of moderate attitudes in students can be increased through the integration of moderate values ​​in the curriculum, interactive teaching methods, and an inclusive social environment. Students who receive a moderation-based curriculum, especially in religious and ethics courses, as well as a social environment that supports plurality, show a more tolerant, wise and open attitude towards differences. A diverse campus environment, support from lecturers through dialogical teaching methods, and students' ability to use technology wisely play an important role in forming a moderate attitude.